2015
DOI: 10.1109/jmems.2014.2343227
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Debris Motion in Vibration Assisted Reverse Micro Electrical Discharge Machining Process (R-MEDM)

Abstract: Reverse microelectrical discharge machining (R-MEDM) process is a recent variant of microelectrical discharge machining process capable of fabricating high aspect ratio arrayed microfeatures and textured surfaces. Efficient flushing of the debris particles from the interelectrode gap is essential for process stability, but extremely small interelectrode gaps (∼5 µm) make the dispelling of debris difficult, rendering the R-MEDM process infeasible for machining difficult-to-erode materials and creation of engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…However, the precise real-time observation of the generation and movement of EDM debris through experiments is difficult. So, analytical and computational modeling have been explored [10,20,116,22,23]. However, these models did not account for the impact force associated with the plasma discharge, which is one of the critical factors affecting the dielectric flow and trajectory of debris particles.…”
Section: Debris Flushing Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise real-time observation of the generation and movement of EDM debris through experiments is difficult. So, analytical and computational modeling have been explored [10,20,116,22,23]. However, these models did not account for the impact force associated with the plasma discharge, which is one of the critical factors affecting the dielectric flow and trajectory of debris particles.…”
Section: Debris Flushing Modelmentioning
confidence: 99%
“…al. [23] recently developed a 2-dimensional, axisymmetric model to study debris motion during the reverse micro-electrical discharge machining process. However, this model did not account for plasma explosion pressure.…”
Section: Debris Flushing Modelmentioning
confidence: 99%
“…Mastud et al set up a simulation model of debris movement with ultrasonic vibration. The study found that the amplitude and frequency make the effect of debris movement and accelerate the debris movement [ 8 ]. Chang et al studied the pressure field, velocity field, and the concentration of debris in machining gap during a period of ultrasonic vibration with Fluent.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al fabricated various shapes of micro tools by R-µEDM and investigated the effects of capacitance and voltage on machining time [3]. Vibration-assisted R-µEDM process for the fabrication of micro-rod has been used and it has been reported that the use of plate electrode with lower thickness leads to an improvement of erosion rate and surface roughness [6]. The Vibration-assisted R-µEDM process is also shown to help in dispelling the debris particles from the inter-electrode gap and this has been illustrated using the simulation model for modelling of debris motion with dielectric flow [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Vibration-assisted R-µEDM process is also shown to help in dispelling the debris particles from the inter-electrode gap and this has been illustrated using the simulation model for modelling of debris motion with dielectric flow [7]. Taguchi based design of experiment has been used to study the effect of process parameters on response measures [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%